Tooth Movement Patterns Based on Traction Methods for Mandibular Canine Retraction Using Skeletal Anchorage: A Finite Element Analysis - Dong-Hwan Lee; Jong-Moon Chae; Jae Hyun Park; Na-Young Chang; Kyung-Hwa Kang; Sung-Kwon Choi (Applied Sciences)
Objective: This study compared the tooth movement patterns of a power arm and a lever jig during mandibular canine retraction into a premolar extraction space using skeletal anchorage. Methods: A finite element model was developed based on anatomical structures. A mini-implant was placed between the mandibular second premolar and first molar, and canine retraction was simulated using a power arm and a lever jig. The lever jig’s vertical arm lengths were 6 mm, 8 mm, and 10 mm, corresponding to force application distances of 4.5 mm, 6.4 mm, and 8.2 mm from the archwire, matching the power arm. Finite element analysis was performed using linear mechanical properties and an explicit method. Results: With the power arm, increasing vertical length led to greater extrusion, while the posterior force remained unchanged. The lever jig also showed increased extrusion with length but to a lesser extent. Posterior force increased proportionally with the lever jig length. Initial displacement analysis showed greater extrusion and distal tipping with the power arm, while the lever jig suppressed extrusion and facilitated controlled tipping. Stress analysis revealed a more uniform periodontal ligament stress distribution with the lever jig. Conclusion: The lever jig minimizes extrusion and enhances force concentration posteriorly, promoting efficient distal movement.